Electrolyte

By introducing high solubility and high stability lithium supplement material MxTy into the electrolyte and regulating the types and quantity of composite anions, the problems of low solubility and poor stability of the existing electrolyte supplement technology are solved, and the effects of efficient lithium supplementation and reducing the impedance of the CEI film layer are achieved, which improves the electrochemical performance and cycle life of the secondary battery.

CN119742452AActive Publication Date: 2025-04-01CALB GROUP CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411939301.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-04-01
Estimated Expiration
2044-12-26

AI Technical Summary

Technical Problem

The existing electrolyte lithium supplement technology has defects such as low solubility, poor system stability and high overall impedance, and cannot effectively replace the lithium supplement technology of the electrode sheet.

Method used

The lithium supplement material MxTy, which has high solubility and high stability, is introduced into the electrolyte, and the mixing entropy of the electrolyte is increased by regulating the type and number of composite anions, thereby achieving efficient lithium supplementation and reducing the impedance of the CEI film layer.

Benefits of technology

It realizes efficient lithium supplementation of electrolyte in secondary batteries, reduces the impedance of the CEI film layer, and improves the overall electrochemical performance and cycle life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005212234730000071
    Figure BDA0005212234730000071
  • Figure BDA0005212234730000081
    Figure BDA0005212234730000081
  • Figure BDA0005212234730000131
    Figure BDA0005212234730000131
Patent Text Reader

Abstract

The invention discloses an electrolyte and belongs to the technical field of batteries, a lithium supplementing material is introduced into the electrolyte, meanwhile, anion composition in components is regulated and controlled, the lithium supplementing material is high in solubility and high in stability, efficient lithium supplementing can be achieved when the electrolyte is applied to a secondary battery, CEI impedance in the battery can be preferably reduced, and the service life of the battery is prolonged. The overall electrochemical performance is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of battery technology, and in particular to an electrolyte. Background Art

[0002] Lithium replenishment technology for lithium-ion batteries refers to the introduction of lithium-containing compounds in addition to the positive electrode active materials in the battery to release active lithium, thereby compensating for the active lithium consumed by the positive electrode active materials when forming the SEI film, thereby reducing the irreversible loss of battery capacity and improving battery cycle performance. At present, the main lithium replenishment technologies are positive electrode replenishment and negative electrode replenishment, that is, setting the lithium replenishment material on the positive electrode sheet or the negative electrode sheet. However, this lithium replenishment technology needs to consider the uniformity and safety of the lithium replenishment material during the production process of the electrode sheet, which increases the preparation cost and increases the difficulty of subsequent recovery of the active materials in the electrode sheet.

[0003] Electrolyte lithium replenishment technology refers to dissolving lithium replenishment materials in the electrolyte and replenishing lithium through lithium ions in the electrolyte. Compared with pole piece lithium replenishment, it is easier to operate, has a larger operating space, and is easier to recycle. However, the current electrolyte lithium replenishment technology is still unable to replace pole piece lithium replenishment technology due to its defects such as low solubility of lithium replenishment materials, poor system stability, and high overall impedance. Summary of the invention

[0004] The purpose of the present application is to overcome the shortcomings of the prior art and provide an electrolyte, wherein the electrolyte introduces a lithium supplement material and simultaneously regulates the anion composition in the components. The lithium supplement material has high solubility and strong stability. When the electrolyte is applied to a secondary battery, efficient lithium supplementation can be achieved. At the same time, the CEI impedance in the battery can be preferably reduced, thereby improving the overall electrochemical performance.

[0005] To achieve the above-mentioned object, in a first aspect of the present application, the present application provides an electrolyte, including a lithium supplement material and a composite anion;

[0006] The lithium supplement material includes M x T y , wherein M includes at least one of Li, Na, and K, T includes at least one of P and S, 1≤x≤3, 1≤y≤8, and x and y are integers;

[0007] The complex anion includes BOB - (bis(oxalatoborate) ion), PO2F2 - (difluorophosphate), ODFB - (difluorooxalatoborate), FSI - (Bis(fluorosulfonyl)imide), TFSI - (Bis(trifluoromethanesulfonyl)imide), ODFP - (difluorobis(oxaloyl)phosphate), FNFSI -([(FSO2)(n-C4F9SO2)N] - )、BF4 - (tetrafluoroborate), PF6 - (hexafluorophosphate), FEA - At least four of (1,1,1-trifluoro-N-[2-[2-(2-methoxyethoxy)ethoxy)]ethyl]methanesulfonamide).

[0008] The beneficial effects of this application are:

[0009] The present application provides an electrolyte, which introduces a lithium-supplementing material and regulates the anion composition in the components. The lithium-supplementing material has high solubility and strong stability. When applied to a secondary battery, the electrolyte can achieve efficient lithium replenishment and can also preferably reduce the CEI impedance in the battery to improve the overall electrochemical performance. DETAILED DESCRIPTION

[0010] In order to make the purpose, technical solutions and advantages of the embodiments of the present application clearer, the technical solutions in the embodiments of the present application are described clearly and completely below. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present application.

[0011] In the present application, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.

[0012] In this application, when it comes to numerical ranges, unless otherwise specified, the above numerical ranges are deemed to be continuous and include the minimum and maximum values ​​of the range, as well as each value between such minimum and maximum values. Further, when a range refers to an integer, each integer between the minimum and maximum values ​​of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be merged. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges included therein.

[0013] The present application is further described below with specific embodiments:

[0014] An electrolyte comprising a lithium supplement material and a composite anion;

[0015] The lithium supplement material includes M x T y , wherein M includes at least one of Li, Na, and K, T includes at least one of P and S, 1≤x≤3, 1≤y≤8, and x and y are integers;

[0016] The complex anion includes BOB - PO2F2 - 、ODFB - 、FSI - TFSI - ODFP - 、FNFSI - 、BF4 - PF6 - 、FEA - At least four of them.

[0017] Compared with the electrode lithium replenishment technology, the electrolyte lithium replenishment technology theoretically has many advantages such as low difficulty in operation, large adjustable space, and convenient recycling. However, in order to achieve sufficient lithium replenishment effect, it is necessary to introduce sufficient lithium-containing compounds into the electrolyte, and at the same time ensure that these compounds will not precipitate before the lithium replenishment is activated. However, since lithium salts exist in traditional electrolytes, the addition of lithium replenishment materials into the electrolyte has a technical bottleneck. In order to solve the above problems, the technical solution of this application introduces lithium replenishment material M into the electrolyte. x T y (It should be noted that the lithium supplement additive M described in this application x T y It is not a pure lithium compound in the traditional sense, but a compound containing metal ions that can realize reversible intercalation and deintercalation behavior in a secondary battery. It can contain but is not limited to lithium ions. It is well known to those skilled in the art that monovalent metal ions such as Li, Na, and K can all realize reversible intercalation and deintercalation during the charge and discharge process, and the main function of the lithium supplement material is to make up for the irreversible active ion loss caused by the formation of the SEI film. The use of non-lithium ion compounds containing Na or K ions can also achieve lithium supplementation in secondary batteries, so it can be used as a lithium supplement material) as a component to supplement active reversible metal ions, and at the same time, anions are oxidized to release electrons to supplement active electrons; in order to improve the solubility and stability of the lithium supplement material in the electrolyte, the technical solution of the present application introduces composite anions for compounding, and the mixing entropy in the overall electrolyte is increased by limiting the number of anion types, and ultimately achieving good electrolyte stability and lithium supplementation effect.

[0018] In addition, M x T y The anions in the electrolyte will be oxidized to form anions during lithium replenishment and form part of the CEI film on the positive electrode. The ion conductivity of this component is poor, which will increase the overall impedance of the CEI film and reduce the overall charge and discharge efficiency of the secondary battery. By constructing a specific composite anion system electrolyte, the entropy disorder can be used to achieve the reaction with M based on the reaction process. x T yA competitive relationship is formed between the anions in the electrolyte and a certain amount of low-impedance inorganic salts are formed on the CEI membrane, which ultimately enables the lithium-supplementing material to be introduced into the electrolyte and achieve a relatively high overall ionic conductivity after lithium replenishment, thereby improving the fast charging performance of the corresponding secondary battery.

[0019] In some embodiments, the number of species of the complex anions in the electrolyte is ≤8.

[0020] Further preferably, the number of types of the complex anions in the electrolyte is in the range of 4, 5, 6, 7, 8 or any two of them.

[0021] As mentioned above, the number of types of composite anions will affect the overall mixing entropy of the electrolyte, thereby affecting the degree of oxidation of anions in the lithium replenishing material and the overall lithium replenishing efficiency of the lithium replenishing material. After optimization, when the number of types of composite anions is within the above range, the lithium replenishing material can achieve the best lithium replenishing effect. At the same time, the electrolyte has high ion transfer efficiency and high stability. After the electrolyte is applied to the secondary battery, the secondary battery has excellent kinetic performance, small impedance and longer cycle life.

[0022] In some embodiments, the complex anion comprises PO2F2 - 、FSI - TFSI - 、FNFSI - 、BF4 - PF6 - 、FEA - At least four of them.

[0023] When compounding composite anions with lithium supplement materials, in addition to considering the mixing entropy in the electrolyte, it is also necessary to consider the application effect of the composite anion itself. When the above-mentioned types of composite anions are preferably used to compound the electrolyte, the stability of the electrolyte at high temperature can be effectively improved, and the probability of side reactions occurring in the secondary battery at high temperature can be reduced, thereby improving its safety and service life at high temperature.

[0024] Further preferably, the composite anion comprises FSI - TFSI - 、FNFSI - and FEA - .

[0025] In addition to the thermal stability of the composite anion, the ionic radius of the composite anion also needs to be considered when compounding the electrolyte, because the size of the ionic radius will lead to differences in the dissociation efficiency of the composite anion and lithium ions, and the ionic conductivity of the electrolyte will also change. When the above composite anion is preferred, the ionic conductivity of the resulting electrolyte can be further improved, and when the electrolyte is used in a secondary battery, better kinetic performance, lower impedance and longer cycle life can be achieved.

[0026] In a specific embodiment of the present application, the complex anion may be derived from a metal salt containing the complex anion, or may be an inorganic and / or organic compound that can be decomposed in an electrolyte solvent and precipitate a corresponding complex anion.

[0027] For example, in some embodiments, the complex anion is derived from a lithium salt containing the corresponding complex anion. More specifically, the FSI - It can come from lithium salt LiFSI.

[0028] In some embodiments, the electrolyte satisfies: 5≤x×n≤14; wherein n is the number of types of complex anions in the electrolyte.

[0029] More preferably, the range value of x×n is one of or any two of 5, 7, 8, 9, 10, 12, and 14.

[0030] Lithium Supplement Material M x T y A Lewis acid-base solvent system is formed between the metal cations, anions and the compounded composite anions. In this system, the unit molar amount of the metal cations in the lithium supplement material affects its own solubility, and also changes the degree of competition between the corresponding anions and the composite anions. When the electrolyte preferably satisfies the above relationship, the electrolyte can maintain the impedance of the positive electrode CEI membrane at a low level while taking into account the higher solubility of the lithium supplement material.

[0031] In some embodiments, the lithium supplement material includes M x P y , the composite anion includes FSI - TFSI - 、FNFSI - 、BF4 - 、FEA - At least four of them.

[0032] When the lithium supplement material contains phosphorus anions, the above-mentioned preferred composite anions are selected for compounding. These anions can improve the diversity of CEI film components when the CEI film is formed at the positive electrode, so that the CEI film has lower impedance and the corresponding secondary battery kinetic performance is better.

[0033] In some embodiments, the lithium supplement material includes M x S y , the composite anion includes PO2F2 - 、FSI - TFSI - and a fourth component, wherein the fourth component is BOB - 、ODFB - ODFP - 、FNFSI - 、BF4 - PF6 - 、FEA - At least one of .

[0034] When the lithium-supplementing material contains sulfur, selecting the above-mentioned preferred composite anions for compounding can effectively further improve the compatibility of the lithium-supplementing material with other components of the electrolyte, thereby making the lithium-supplementing effect of the material better.

[0035] In some embodiments, the lithium supplement material includes at least one of Li3P, Li4P, Li5P, Li6P, Li7P, Li7P3, Li2S4, Li2S6, and Li2S8.

[0036] In some embodiments, the electrolyte further includes a solvent.

[0037] In some embodiments, the solvent includes at least one of a carbonate solvent, a carboxylate solvent, an ether solvent, a sulfone solvent, a nitrile solvent, and a phosphate solvent.

[0038] Exemplarily, the carbonate solvent includes but is not limited to at least one of propylene carbonate (PC), ethylene carbonate (EC), dimethyl carbonate (DMC), diethyl carbonate (DEC), and ethyl methyl carbonate (EMC); the carboxylate solvent includes but is not limited to at least one of ethyl acetate, methyl formate, and 1,4-butyrolactone; the ether solvent includes at least one of dimethyltetrahydrofuran, tetrahydrofuran, and 1,2-dimethoxyethane; the sulfone solvent includes at least one of methyl sulfone and dimethyl sulfoxide; the nitrile solvent includes at least one of propionitrile, butyronitrile, 1-(2-cyanoethyl)pyrrole, and 1,3,6-hexanetrinitrile; the phosphate solvent includes at least one of trimethyl triphosphate and triethyl phosphate.

[0039] Further preferably, the solvent may also include but is not limited to at least one of fluorinated derivatives of carbonate solvents, fluorinated derivatives of carboxylate solvents, fluorinated derivatives of ether solvents, fluorinated derivatives of sulfone solvents, fluorinated derivatives of nitrile solvents, and fluorinated derivatives of phosphate solvents.

[0040] Illustratively, the fluorinated derivative of carbonate solvent includes, but is not limited to, fluoroethylene carbonate (FEC).

[0041] The embodiment described in the present application also provides a secondary battery, including the electrolyte described in the present application.

[0042] In some embodiments, the battery further includes a positive electrode sheet and a negative electrode sheet; the positive electrode sheet includes a positive electrode material, and the negative electrode sheet includes a negative electrode material.

[0043] In some embodiments, the positive electrode sheet includes a current collector and a positive electrode material layer;

[0044] Further preferably, the positive electrode material layer comprises a positive electrode material, a binder and a conductive agent.

[0045] In some embodiments, the negative electrode sheet includes a current collector and a negative electrode material layer;

[0046] Further preferably, the negative electrode material layer comprises a negative electrode material, a binder, a thickener and a conductive agent.

[0047] In some embodiments, the positive electrode material comprises at least one of lithium nickel cobalt manganese oxide, lithium nickel cobalt manganese oxide mixed with lithium iron phosphate, lithium iron phosphate, lithium iron phosphate mixed with lithium iron manganese phosphate, and lithium iron manganese phosphate.

[0048] The electrolyte described in the present application is universal when matched with positive electrode materials, and mainly relies on the mixing entropy regulation and interaction between lithium replenishing materials and composite anions. Whether it is a ternary material, or a lithium iron phosphate system or lithium iron manganese phosphate system positive electrode material, it can effectively improve its lithium replenishment effect and stability during application, so that the final secondary battery has excellent electrochemical properties.

[0049] In some embodiments, the positive electrode material includes at least one of lithium nickel cobalt manganese oxide and doped lithium nickel cobalt manganese oxide, and in the electrolyte, the lithium supplement material includes Li3P.

[0050] Further preferably, the lithium supplement material includes Li3P, and the composite anion includes BOB - PO2F2 - 、BF4 - and PF6 - .

[0051] When the positive electrode material includes a ternary material, selecting Li3P, a lithium-supplementing material having an oxidation potential lower than the delithiation potential of the ternary material, can make the oxidation time node of the lithium-supplementing material later when the positive electrode CEI film is formed, thereby having a better control level on the impedance of the CEI film; on the other hand, the above-mentioned preferred composite anion can further cooperate with the ternary material and inhibit the dissolution of transition metal ions in the ternary material, and the CEI film component formed thereby has a better protective effect on the positive electrode material, better interface stability, and better cycle stability of the resulting secondary battery.

[0052] In some embodiments, the positive electrode material includes at least one of lithium iron phosphate and doped lithium iron phosphate, and in the electrolyte, the lithium supplement material includes Li2S4.

[0053] Further preferably, the composite anion comprises FSI - TFSI - 、FNFSI - and FEA - .

[0054] The delithiation potential of lithium iron phosphate materials is around 3.2V. When Li2S4 is preferred as the lithium supplement material, in addition to slowing down the formation of nodes of S element on the CEI membrane and reducing the impedance of the CEI membrane, the above-mentioned preferred composite anions can also be compounded to enhance the thermal stability of the overall electrolyte, give full play to the advantages of lithium iron phosphate materials, and further enhance the long-term thermal stability of the final secondary battery.

[0055] In some embodiments, the positive electrode material includes at least one of lithium iron manganese phosphate and doped lithium iron manganese phosphate, and in the electrolyte, the lithium supplement material includes Li5P.

[0056] Further preferably, the composite anion comprises PO2F2 - 、FSI - TFSI - 、FNFSI - and PF6 - .

[0057] When Li5P is preferably used as a lithium supplement material for compounding lithium iron manganese phosphate materials, the oxidation potential of this component is lower than the delithiation potential of the lithium iron manganese phosphate positive electrode material, so the CEI film impedance of the positive electrode sheet can be lower and the compatibility with the positive electrode sheet is better.

[0058] In some embodiments, in the electrolyte, the mass content of the lithium supplement material is 0.01 to 15% based on the total mass of the electrolyte.

[0059] In some specific embodiments, the partial structure of the lithium supplement material is shown in the following formula I-1 to formula I-8:

[0060]

[0061]

[0062] It should be noted that in the technical solution of this application, the type and mass content of the lithium supplement material are confirmed by high performance liquid chromatography-mass spectrometry, and the specific method is as follows:

[0063] The electrolyte samples were injected into the Agilent Infinity III liquid chromatography-mass spectrometer (LC-MS) using a microinjector for type (qualitative) and content (quantitative) testing:

[0064] ① Obtaining the MS standard curve and LC peak area-concentration curve: Formula I-1 to I-8 are prepared into EMC solutions of different concentrations, and injected into the above-mentioned liquid chromatography-mass spectrometry instrument, respectively, to obtain the MS spectrum and LC spectrum of the standard substance, and integrate the peak area in the LC spectrum (the test software routinely processes the test data) to obtain the peak area. A linear graph is drawn between the peak area and concentration of the standard substance of different concentrations to obtain a standard LC peak area-concentration curve.

[0065] ② Determine the type: inject the electrolyte to be tested into the above-mentioned liquid chromatography-mass spectrometer to obtain the LC spectrum and MS spectrum of the electrolyte to be tested. Compare the MS spectrum of the electrolyte to be tested with the MS spectrum of the standard to determine whether the electrolyte to be tested contains additives of formulas I-1 to I-8 (for example, if the MS spectrum of the electrolyte to be tested has a corresponding peak at the position of the peak of formula I-1 in the standard spectrum, it is determined that the electrolyte to be tested contains the lithium supplement additive of formula I-1, and the same applies to other components).

[0066] ③Determination of quality content:

[0067] The peak area is obtained by integrating the peaks in the LC spectrum of the electrolyte to be tested. According to the standard LC peak area-concentration curve, the concentration of the substance to be tested can be obtained if the peak area is known.

[0068] When the electrolyte is present in the secondary battery, the electrolyte is collected by the following method:

[0069] First, discharge the secondary battery: Use battery charging and discharging equipment to discharge the battery. Discharge conditions: current 0.3C, cut-off voltage is set according to the characteristics of the active material system, for example: lithium iron phosphate / graphite system: 2.5V;

[0070] Lithium manganese iron phosphate / graphite system: 2.5V;

[0071] Lithium nickel cobalt manganese oxide / graphite system: 2.8V;

[0072] Lithium nickel cobalt manganese oxide / silicon-based system: 2.8V;

[0073] After recording the battery number / barcode, disassemble the battery in a glove box (H2O ≤ 0.1 ppm, O2 ≤ 0.1 ppm) to collect the electrolyte.

[0074] Collecting the electrolyte: There are the following two methods for collecting the electrolyte: After removing the battery cover plate, ① If there is free electrolyte, use a pipette to collect the electrolyte into a 5 mL sample tube and seal it with sealing tape to prevent electrolyte leakage. ② If there is no free electrolyte, a hydraulic press (FY-30 hydraulic press from Beijing Heng'aode Technology Co., Ltd.) can be used to continuously apply pressure until free electrolyte appears, and then collect the electrolyte into the sample tube and seal it.

[0075] In some embodiments, in the electrolyte, the test method for the type quantity of the composite anion and the mass content of the salt containing the composite anion is as follows:

[0076] Determine the type and concentration of anions: Inject the collected electrolyte into the sample pool of a Thermo Fisher Dionex TM Aquion TM IC ion chromatograph, test the ion chromatogram curve of the electrolyte sample, and determine the type (quantity) of the composite anion by comparing with the database built in the chromatograph; determine the concentration corresponding to the salt containing the anion, that is, the mass content, through the peak area curve (peak area-concentration curve).

[0077] When the electrolyte exists in a secondary battery, the same method as above is used to collect the electrolyte, which will not be elaborated here.

[0078] In some embodiments, the mass content of the salt containing the composite anion corresponding to the composite anion in the electrolyte is 1-20%.

[0079] In some embodiments, at least one of the lithium nickel cobalt manganese oxide and the doped lithium nickel cobalt manganese oxide includes LiNi a Mn b Co c N d O2, where 0 < a < 1, 0 < b < 1, 0 < c < 1, 0 ≤ d < 0.1, a + b + c + d = 1 and N is at least one of Al, Na, Ti, Nb, Zr, W, Fe, Cr.

[0080] In some embodiments, the lithium iron manganese phosphate includes LiFe e Mn f PO4, where 0 < e < 1, 0 < f < 1, e + f = 1.

[0081] In some embodiments, the negative electrode material includes at least one of a carbon-based material, a silicon-based material, and lithium titanate.

[0082] Exemplarily, the carbon-based material may be at least one of natural graphite, artificial graphite, mesophase carbon microbeads, hard carbon, and soft carbon; the silicon-based material may be at least one of elemental silicon, silicon oxide, and a silicon-carbon composite material.

[0083] Those skilled in the art may also adopt other methods to prepare negative electrode materials according to actual conditions, or directly purchase commercially available products.

[0084] The present invention is further described below with specific examples, which are not to be construed as limiting the scope of the present invention:

[0085] Example 1

[0086] A battery, the preparation method comprising the following steps:

[0087] (1) Preparation of positive electrode sheet: The positive electrode material is lithium nickel cobalt manganese oxide LiNi 0.6 Mn 0.2 Co 0.2 O2, conductive agent SP and binder polyvinylidene fluoride are dispersed in N-methylpyrrolidone in a mass ratio of 97.8:1.2:1, and the slurry is prepared by vacuum stirring, and then coated on both sides of the current collector aluminum foil, and then rolled and cut to obtain the positive electrode sheet;

[0088] (2) Preparation of negative electrode sheet: artificial graphite of negative electrode material, conductive agent SP, thickener sodium carboxymethyl cellulose, and binder styrene butadiene rubber are dispersed in water at a mass ratio of 96.5:2.2:0.2:1.1, and the slurry is prepared by vacuum stirring, and then coated on both sides of the current collector copper foil, and then rolled and cut to obtain the negative electrode sheet;

[0089] (3) Preparation of diaphragm: A PP diaphragm with an average pore size of 2 μm and an air permeability of 300 s / 100 mL is used, and an alumina ceramic coating is provided on the diaphragm;

[0090] (4) Preparation of electrolyte: Ethylene carbonate, ethyl methyl carbonate and diethyl carbonate were mixed in a volume ratio of 3:5:2 as a solvent; then lithium salts containing specific complex anions in the mass content recorded in Table 1 were added respectively, and finally lithium supplementing materials were added and mixed evenly to obtain the electrolyte, as shown in Table 1, where n is the BOB content of the electrolyte. - PO2F2 - 、ODFB - 、FSI - TFSI - ODFP - 、FNFSI- 、BF4 - PF6 - 、FEA - The number of types of these composite anions, x is the unit mole number of the metal element in the lithium supplement material (for example, when the lithium supplement material is Li3P7, x=3).

[0091] (5) The positive electrode sheet, the separator (the coating surface faces the positive electrode sheet), and the negative electrode sheet are stacked and wound in order to form a battery cell (the alumina coating of the separator faces the positive electrode), and the battery cell is placed in an outer packaging shell, and after drying, an electrolyte is injected, and after vacuum packaging, standing, forming, and constant capacity, the battery is obtained.

[0092] Embodiments 2 to 18

[0093] A battery, the only difference from Example 1 is that the components of the electrolyte are different, and the results are shown in Table 1.

[0094] Embodiment 19

[0095] A battery, the preparation method comprising the following steps:

[0096] (1) Preparation of positive electrode sheet: The positive electrode material lithium iron phosphate LiFePO4, the conductive agent SP and the binder polyvinylidene fluoride are dispersed in N-methylpyrrolidone at a mass ratio of 97.8:1.2:1, and the slurry is prepared by vacuum stirring, and then coated on both sides of the current collector aluminum foil, and then rolled and cut to obtain the positive electrode sheet;

[0097] (2) Preparation of negative electrode sheet: artificial graphite of negative electrode material, conductive agent SP, thickener sodium carboxymethyl cellulose, and binder styrene butadiene rubber are dispersed in water at a mass ratio of 96.5:2.2:0.2:1.1, and the slurry is prepared by vacuum stirring, and then coated on both sides of the current collector copper foil, and then rolled and cut to obtain the negative electrode sheet;

[0098] (3) Preparation of the diaphragm: A PP diaphragm with an average pore size of 2 μm and an air permeability of 300 s / 100 mL is used; the diaphragm is provided with an alumina ceramic coating;

[0099] (4) Preparation of electrolyte: Ethylene carbonate, ethyl methyl carbonate and diethyl carbonate were mixed in a volume ratio of 3:5:2 as a solvent; then lithium salts containing specific complex anions in amounts recorded in Table 1 were added respectively, and finally a lithium supplement material in a specific amount was added and mixed evenly to obtain the electrolyte;

[0100] (5) The positive electrode sheet, the separator (with the coating surface facing the positive electrode sheet), and the negative electrode sheet are stacked and wound in order to form a battery cell, and the battery cell is placed in an outer packaging shell, and after drying, an electrolyte is injected, and after vacuum packaging, standing, forming, and constant capacity, the battery is obtained.

[0101] Embodiments 20 to 28

[0102] A battery, the only difference from Example 19 is that the components of the electrolyte are different, and the results are shown in Table 1.

[0103] Embodiment 29

[0104] A battery, the preparation method comprising the following steps:

[0105] (1) Preparation of positive electrode sheet: The positive electrode material is lithium manganese iron phosphate LiFe 0.5 Mn 0.5 PO4, conductive agent SP and binder polyvinylidene fluoride are dispersed in N-methylpyrrolidone in a mass ratio of 97.8:1.2:1, and the slurry is prepared by vacuum stirring, and then coated on both sides of the current collector aluminum foil, and then rolled and cut to obtain the positive electrode sheet;

[0106] (2) Preparation of negative electrode sheet: artificial graphite of negative electrode material, conductive agent SP, thickener sodium carboxymethyl cellulose, and binder styrene butadiene rubber are dispersed in water at a mass ratio of 96.5:2.2:0.2:1.1, and the slurry is prepared by vacuum stirring, and then coated on both sides of the current collector copper foil, and then rolled and cut to obtain the negative electrode sheet;

[0107] (3) Preparation of diaphragm: A PP diaphragm with an average pore size of 2 μm and an air permeability of 300 s / 100 mL was used;

[0108] (4) Preparation of electrolyte: Ethylene carbonate, ethyl methyl carbonate and diethyl carbonate were mixed in a volume ratio of 3:5:2 as a solvent; then lithium salts containing specific complex anions in amounts recorded in Table 1 were added respectively, and finally a lithium supplement material in a specific amount was added and mixed evenly to obtain the electrolyte;

[0109] (5) The positive electrode sheet, the separator, and the negative electrode sheet are stacked and wound in order to form a battery cell, and the battery cell is placed in an outer packaging shell, and after drying, an electrolyte is injected, and after vacuum packaging, standing, forming, and constant capacity, the battery is obtained.

[0110] Embodiments 30 to 36

[0111] A battery, the only difference from Example 29 is that the components of the electrolyte are different, and the results are shown in Table 1.

[0112] Embodiment 37

[0113] A battery, the only difference from Example 1 is that the components of the electrolyte are different, and the results are shown in Table 1.

[0114] Comparative Examples 1 to 3

[0115] A battery, the only difference from Example 1 is that the components of the electrolyte are different, and the results are shown in Table 1.

[0116] Comparative Examples 4 to 6

[0117] A battery, the only difference from Example 19 is that the components of the electrolyte are different, and the results are shown in Table 1.

[0118] Comparative Examples 7 to 9

[0119] A battery, the only difference from Example 29 is that the components of the electrolyte are different, and the results are shown in Table 1.

[0120] Table 1

[0121]

[0122]

[0123]

[0124]

[0125]

[0126] Effect example

[0127] The batteries obtained in each embodiment and comparative example were tested as follows:

[0128] (1) Positive electrode CEI impedance test: The battery is charged at a constant current and constant voltage of 0.3C on the LAND charge and discharge system to the upper limit voltage, with a cut-off current ≤ 0.05C; then discharged at a rate of 0.3C to the lower limit voltage, and the above steps are repeated 3 times, with the actual discharge capacity of the third time as the discharge capacity of the battery; then charged at a rate of 0.3C to 50% of the third discharge capacity; based on the different positive electrode materials used in the battery, the upper and lower limits of the working voltage are different:

[0129] LiFePO4: 2.5V~3.65V; LiFe 0.5 Mn 0.5 PO4: 2.5V~4.25V;

[0130] LiNi 0.6 Mn 0.2 Co 0.2 O2: 2.8V~4.25V;

[0131] Among them, Examples 1 to 18, Example 37, and Comparative Examples 1 to 3 correspond to 2.8 to 4.25 V; Examples 19 to 28 and Comparative Examples 4 to 6 correspond to 2.5 to 3.65 V; Examples 29 to 36 and Comparative Examples 7 to 9 correspond to 2.5 to 4.25 V;

[0132] Then remove the battery, wrap the pole ear with insulating glue and transfer it to a vacuum glove box (H2O≤0.01ppm, O2≤0.01ppm), disassemble the positive electrode, place it in a polytetrafluoroethylene box containing DMC for cleaning, dry it naturally, cut it into discs with a diameter of 9 mm and seal it; stack the discs with the same type of diaphragm and the same type of electrolyte in the batteries obtained in each embodiment and comparative example in the order of disc, electrolyte (10μL), diaphragm, electrolyte (10μL), and disc, and assemble a symmetrical battery. After standing for 24 hours, use a CS310X multi-channel electrochemical workstation to test the impedance spectrum under the conditions of amplitude 5mV and frequency 100000-0.1Hz; after obtaining the impedance spectrum, select the value of the horizontal axis when -Z"=0 as R1, and the inflection point of the ellipse, that is, the minimum value of the curve is R2; the impedance of the positive electrode CEI is R=R2-R1

[0133] (2) Cycle capacity retention rate: Set the working environment to 60°C, charge the battery on the LAND charging and discharging system at a constant current and constant voltage of 1C to the upper limit voltage, and the cut-off current is less than or equal to 0.05C; then discharge at a rate of 1C to the lower limit voltage; repeat the above steps 1000 times, and calculate the discharge capacity of the 1000th time. The discharge capacity retention rate (%) after 1000 cycles = 100% × discharge capacity A1 at 1000 cycles / discharge capacity A0 at the first cycle;

[0134] Based on the different positive electrode materials used in the battery, the upper and lower limits of the operating voltage are different:

[0135] LiFePO4: 2.5V~3.65V; LiFe 0.5 Mn 0.5 PO4: 2.5V~4.25V;

[0136] LiNi 0.6 Mn 0.2 Co 0.2 O2: 2.8V~4.25V.

[0137] Among them, Examples 1 to 18, Example 37, and Comparative Examples 1 to 3 correspond to 2.8 to 4.25 V; Examples 19 to 28 and Comparative Examples 4 to 6 correspond to 2.5 to 3.65 V; Examples 29 to 36 and Comparative Examples 7 to 9 correspond to 2.5 to 4.25 V.

[0138] The test results are shown in Table 2.

[0139] Table 2

[0140]

[0141]

[0142] From Table 2 we can see that:

[0143] (1) When the electrolyte described in the present application is applied to a secondary battery, it can achieve efficient lithium replenishment and reduce the impedance of the CEI film layer in the battery. The CEI film impedance on the positive electrode sheet in the ternary system secondary battery corresponding to the products of Examples 1 to 18 can be maintained in the range of 66mΩ, and the capacity retention rate after 1000 cycles at 1C rate can reach more than 78%, and the highest can reach more than 86%; the CEI film impedance on the positive electrode sheet in the lithium iron phosphate system secondary battery corresponding to Examples 19 to 28 can be maintained in the range of 47mΩ, and the capacity retention rate after 1000 cycles at 1C rate can reach more than 85%, and the highest can reach more than 88%; the CEI film impedance on the positive electrode sheet in the lithium iron manganese phosphate system secondary battery corresponding to Examples 29 to 36 can be maintained in the range of 45mΩ, and the capacity retention rate after 1000 cycles at 1C rate can reach more than 85%. It can reach more than 78.5%, and the highest can reach more than 81%. This is mainly due to the application of lithium-supplementing materials in the electrolyte and the specific selection of composite anions, which enables the lithium-supplementing materials to achieve good solubility and stability in the electrolyte, and based on the entropy disorder, a competitive relationship is formed with the anions in the lithium-supplementing materials, and a certain amount of low-impedance inorganic salts are formed on the CEI membrane, so that the electrolyte can ultimately maintain a relatively high overall ionic conductivity after lithium replenishment, thereby improving the fast charging performance of the corresponding secondary battery; in contrast, although the comparative examples also introduce composite anions, due to insufficient number of types or improper type selection, regardless of whether the total amount of additives is the same as that of the example products, the ideal entropy disorder of the electrolyte system cannot be achieved, the formed CEI membrane has a high impedance, and the cycle life of the secondary battery is far inferior to that of the example products.

[0144] (2) According to the comparison between the products in Examples 1 to 18, it can be seen that the selection includes FSI - TFSI - 、FNFSI - and FEA - The composite anions including BOB can achieve better battery kinetics and cycle life based on the optimization of ion radius. When the positive electrode material includes ternary materials, the selection of LiP3, a lithium-supplementing material having an oxidation potential lower than the delithiation potential of the ternary materials, can make the oxidation time node of the lithium-supplementing material later when the positive electrode CEI film is formed, thereby having a better control level on the impedance of the CEI film. On the other hand, when LiP3 is selected as the lithium-supplementing material, it can be seen from Examples 4 to 7 that BOB is further preferably included. -PO2F2 - 、BF4 - and PF6 - The composite anions contained therein cooperate with the ternary materials to effectively inhibit the dissolution of transition metal ions in the ternary materials, and the CEI membrane components formed thereby have better protection effects on the positive electrode materials, better interface stability, and better cycle performance of the resulting secondary battery.

[0145] Lithium Supplement Material M x T y The metal cations, anions and the compounded composite anions in the lithium supplement material form a Lewis acid-base solvent system. The unit molar amount of the metal cations in the lithium supplement material affects its solubility, and also changes the degree of competition between the corresponding anions and the composite anions. When the product of the unit molar number of the metal element in the lithium supplement material and the number of types of composite anions in the electrolyte is preferably 5 to 14, the corresponding battery comprehensive performance will also be better. The number of types of composite anions itself will affect the overall mixing entropy of the electrolyte, thereby affecting the oxidation degree of anions in the lithium supplement material and the overall lithium supplement efficiency of the lithium supplement material. When the number of types of composite anions is within 8, the lithium supplement material can achieve a better lithium supplement effect. At the same time, the electrolyte has a high ion transmission efficiency and high stability. The secondary battery after the electrolyte is applied to the secondary battery has excellent kinetic performance, small impedance and longer cycle life.

[0146] (3) According to the products of Examples 19 to 28 and Examples 29 to 36, it can be seen that when the corresponding battery systems are lithium iron phosphate system and lithium iron manganese phosphate system, the lithium supplement materials corresponding to the electrolyte are Li2S4 and LiP5, which have better effects. This is because the lithium de-lithiation potential of lithium iron phosphate materials is about 3.2V. When Li2S4 is used as the lithium supplement material, it can not only slow down the formation of S single substance on the CEI film and reduce the impedance of the CEI film, but also reduce the resistance of the CEI film. - TFSI - 、FNFSI - and FEA - When LiP5 is used as a lithium supplement material for compounding lithium iron phosphate materials, the oxidation potential of this component is lower than the delithiation potential of lithium iron phosphate positive electrode materials, so it can also reduce the impedance of the CEI film. - 、FSI - TFSI - 、FNFSI - and PF6 - The composite anions included can achieve better electrochemical performance.

Claims

1. An electrolyte, characterized in that: Including lithium supplement materials and composite anions; The lithium supplement material includes M x T y , wherein M includes at least one of Li, Na, and K, T includes at least one of P and S, 1≤x≤3, 1≤y≤8, and x and y are integers The complex anion includes BOB - PO2F2 - 、ODFB - 、FSI - TFSI - ODFP - 、FNFSI - 、BF4 - PF6 - 、FEA - At least four of them.

2. The electrolyte according to claim 1, characterized in that The number of types of the composite anions in the electrolyte is ≤8.

3. The electrolyte according to claim 1, characterized in that The composite anion includes PO2F2 - 、FSI - TFSI - 、FNFSI - 、BF4 - PF6 - 、FEA - At least four of; preferably, the complex anion includes FSI - TFSI - 、FNFSI - and FEA - .

4. The electrolyte according to claim 1, characterized in that The electrolyte satisfies: 5≤x×n≤14; Where n is the number of complex anions in the electrolyte.

5. The electrolyte according to claim 1, characterized in that The lithium supplement material includes M x P y , the composite anion includes FSI - TFSI - 、FNFSI - 、BF4 - 、FEA - At least four of them.

6. The electrolyte according to claim 1, characterized in that The lithium supplement material includes M x S y , the composite anion includes PO2F2 - 、FSI - TFSI - and a fourth component, wherein the fourth component is BOB - 、ODFB - ODFP - 、FNFSI - 、BF4 - PF6 - 、FEA - At least one of .

7. A secondary battery, characterized in that: It comprises the electrolyte according to any one of claims 1 to 6; the secondary battery further comprises a positive electrode sheet and a negative electrode sheet; the positive electrode sheet comprises a positive electrode material, and the negative electrode sheet comprises a negative electrode material.

8. The secondary battery according to claim 7, characterized in that: The positive electrode material comprises at least one of lithium nickel cobalt manganese oxide, doped lithium nickel cobalt manganese oxide, lithium iron phosphate, doped lithium iron phosphate, lithium iron manganese phosphate, and doped lithium iron manganese phosphate.

9. The secondary battery according to claim 8, characterized in that: The positive electrode material includes at least one of lithium nickel cobalt manganese oxide and doped lithium nickel cobalt manganese oxide. In the electrolyte, the lithium supplement material includes Li3P. Preferably, the composite anion includes BOB - PO2F2 - 、BF4 - and PF6 - .

10. The secondary battery according to claim 8, characterized in that: The positive electrode material includes at least one of lithium iron phosphate and doped lithium iron phosphate. In the electrolyte, the lithium supplement material includes Li2S4; preferably, the composite anion includes FSI - TFSI - 、FNFSI - and FEA - .

11. The secondary battery according to claim 8, characterized in that: The positive electrode material includes at least one of lithium iron manganese phosphate and doped lithium iron manganese phosphate. In the electrolyte, the lithium supplement material includes Li5P; preferably, the composite anion includes PO2F2 - 、FSI - TFSI - 、FNFSI - and PF6 - .

Citation Information

Patent Citations

  • Electrolyte for Li-S battery, preparation method thereof, and Li-S battery containing same

    CN102983361A

  • Capacity compensation type electrolyte additive, preparation method, application, electrolyte containing additive and secondary battery

    CN114614088A

  • Preparation method of sodium ion start-stop battery with ultra-wide working temperature area

    CN117673482A

  • Capacity-compensation electrolyte additive, preparation method and application, electrolyte containing the same, and secondary battery

    US20230223597A1